Utilization of the Bukuwarung Application as a Digital Financial Recording Solution for Fashion Msmes In Ciledug - Monica, Laura; Meiliya, Nailil Muna; Busyra, Nur (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study investigates the urgent need for digital transformation in financial management among Micro, Small, and Medium Enterprises (MSMEs), particularly within the fashion sector in Ciledug, in response to the demands of the Society 5.0 era. The research aims to address the challenges MSMEs face in maintaining accurate financial records and explores the implementation of the BukuWarung application as a practical digital solution. Method: The study employed a participatory approach involving four fashion MSMEs: Rangkayo 2, Rangkayo 3, Rangkayo 4, and 5758 PL. The intervention was conducted through a series of stages including initial surveys, socialization, hands-on training, continuous monitoring, and final evaluation. Data were collected qualitatively through observation and feedback during the assistance process. Practical Applications: The findings demonstrate that the BukuWarung application significantly enhances MSMEs’ ability to digitally record financial transactions such as income, expenses, receivables, payables, and inventory. The application contributes to the creation of more accurate and transparent financial reports, thereby improving digital financial literacy and operational efficiency. It also supports waste recovery and better resource management in small-scale businesses. Conclusion: The study concludes that digital financial tools like BukuWarung can effectively empower MSMEs in adopting modern financial practices. Despite minor technical challenges and initial resistance to routine recording, the overall impact of the intervention was positive, indicating a meaningful step toward sustainable digital transformation in the MSME sector.